Successful time management : how to be organized, productive and get things done - Forsyth, Patrick (Creating Success Ser., 2022)
"Successful Time Management is packed with proven tips, tools and techniques to help you review and assess your time management and adopt new work practices to improve it. This book includes great time-saving ideas, practical solutions and checklists, plus advice on: controlling paperwork, organizing your emails, delegating and working with others, prioritizing to focus on key issues, getting and staying organized. This fully updated 6th edition features even more practical exercises, useful templates and top tips to help you minimize time-wasting and interruptions, and focus on the priorities that will lead to success in your job and career. Successful Time Management will give you the tools to become more efficient and effective. The Creating Success series of books... Unlock vital skills, power up your performance and get ahead with the bestselling Creating Success series. Written by experts for new and aspiring managers and leaders, this million-selling collection of accessible and empowering guides will get you up to speed in no time. Packed with clever thinking, smart advice and the kind of winning techniques that really get results, you'll make fast progress, quickly reach your goals and create lasting success in your career"--